Reversing the Route: from Watching a Short Film to the Literary Text - Κοτρώνης, Δημήτρης; Σπαντιδάκης, Ιωάννης (Education Sciences, 2024)
The majority of well-known literary narratives for children have now been visualized and transformed into multimedia texts, resulting in a dominance of watching over reading. However, these are distinct processes with different outcomes in the development of skills required for understanding and producing narrative texts. Visualized narratives can contribute to the comprehension and production of narrative texts, but they are effective when approached as multimedia texts: viewing does not remain a passive process and is transformed into a learning process as it is enriched with complementary activities outside the video (worksheets) or within the video (interactive video). In this way, visual storytelling is transformed into textual narration and compared with the literary text. Therefore, the alternative path for children to engage with literary texts may be the reverse: from watching animations to the literary text that dictated the multimedia narrative.